Parallel computing via message passing: comparison between Microsoft MPI and Klyng framework / Nik Nasrul Faiz Nik Yahaya - Nik Yahaya, Nik Nasrul Faiz (Faculty of Computer and Mathematical Sciences, 2017)
Parallel Computing is an architecture that allow multiprocessing and multithreading to increase the speed of complex computation involving large data analysis by implementing concurrent programming. Due to the practice of traditional serial computing, parallel computing extend any possible programming language to provide a framework such as message passing to enable shared and distributed memory computing. Message passing is one of the most popular techniques to deploy such architectures. The emergence of MPI standard that outlined necessaries library for a message passing to work, liven the hope of parallel community. Hence, several implementations of MPI such as Microsoft MPI rise to overcome the time consuming issues of serial computing. The unpopular and yet unrecognized JavaScript framework named Klyng that also implement MPI framework, is studied and discussed in this paper. Microsoft MPI that have been implemented widely is also deliberated and become the benchmark to compare the performance and ability of JavaScript to operate parallel computing via message passing.